The association between self-reported and clinically determined hypomanic symptoms and the onset of major mood disorders. Issue 2 (March 2017) - Goodday, Sarah Margaret; Preisig, Martin; Gholamrezaee, Mehdi; Grof, Paul; Angst, Jules; Duffy, Anne
Abstract : Background: Hypomanic symptoms may be a useful predictor of mood disorder among young people at high risk for bipolar disorder. Aims: To determine whether hypomanic symptoms differentiate offspring of parents with bipolar disorder (high risk) and offspring of well parents (control) and predict the development of mood episodes. Method: High-risk and control offspring were prospectively assessed using semi-structured clinical interviews annually and completed the Hypomania Checklist-32 Revised (HCL-32). Clinically significant sub-threshold hypomanic symptoms (CSHS) were coded. Results: HCL-32 total and active or elated scores were higher in control compared with high-risk offspring, whereas 14% of high-risk and 0% of control offspring had CSHS. High-risk offspring with CSHS had a fivefold increased risk of developing recurrent major depression ( P =0.0002). The median onset of CSHS in high-risk offspring was 16.4 (6–31) years and was before the onset of major mood episodes. Conclusions: CSHS are precursors to major mood episodes in high-risk offspring and could identify individuals at ultra-high risk for developing bipolar disorder.